Local Income Inequality, Individual Socioeconomic Status, and Unmet Healthcare Needs in Ohio, USA - Dmitry Tumin; Michelle Menegay; Michelle Menegay; Emily A. Shrider; Michael Nau; Rachel Tumin (Mary Ann Liebert, 2018)
Purpose: Income inequality has been implicated as a potential risk to population health due to lower provision of healthcare services in deeply unequal countries or communities. We tested whether county economic inequality was associated with individual self-report of unmet healthcare needs using a state health survey data set. Methods: Adults residents of Ohio responding to the 2015 Ohio Medicaid Assessment Survey were included in the analysis. Ohio's 88 counties were classified into quartiles according to the Gini coefficient of income inequality. The primary outcome was a composite of self-reported unmet dental care, vision care, mental healthcare, prescription medication, or other healthcare needs within the past year. Unmet healthcare needs were compared according to county inequality quartile using weighted logistic regression. Results: The analytic sample included 37,140 adults. The weighted proportion of adults with unmet healthcare needs was 28%. In multivariable logistic regression, residents of counties in the highest (odds ratio [OR]=1.13, 95% confidence interval [CI]: 1.01?1.26; p=0.030) and second-highest (OR=1.16, 95% CI: 1.04?1.30; p=0.010) quartiles of income inequality experienced more unmet healthcare needs than residents of the most equal counties. Conclusion: Higher county-level income inequality was associated with individual unmet healthcare needs in a large state survey. This finding represents novel evidence for an individual-level association that may explain aggregate-level associations between community economic inequality and population health outcomes.